Melatonin Therapy Improves Cardiac Autonomic Modulation in Pinealectomized Patients - Campos, Luciana Aparecida; Bueno, Clarissa; Barcelos, Isabella P.; Halpern, Bruno; Brito, Leandro C.; Amaral, Fernanda G.; Baltatu, Ovidiu Constantin; Cipolla-Neto, José (Frontiers in Endocrinology, 2020)
The purpose of this investigational study was to assess the effects of melatonin replacement therapy on cardiac autonomic activity in pinealectomized patients. This was an open-label, single-arm, single-center, proof-of-concept study consisting of a screening period, a 3-month treatment period with melatonin (3 mg/day), and a 6-month washout period. The cardiac autonomic function was determined through heart rate variability (HRV) measures during polysomnography. Pinealectomized patients (n=5) with confirmed absence of melatonin were included in this study. Melatonin treatment increased vagal-dominated HRV indices including RMSSD (root mean square of the R-R successive differences: 39.7 ms [95%CI 2.0 to 77.4], p=0.04), pNN50 (% of successive R-R intervals that differ by more than 50 ms: 17.1% [95%CI 9.1 to 25.1], p=0.003), HF-band power (absolute power of the high-frequency band: 1390 ms2 [95%CI 511.9 to 2267], p=0.01) and also sympathetic HRV indices like SDNN (standard deviation of R-R intervals: 57.6 ms [95%CI 15.2 to 100.0], p=0.02) and LF-band power (absolute power of the low-frequency band: 4592 ms2 [95%CI 895.6 to 8288], p=0.03). These HRV indices returned to pretreatment values when melatonin treatment was discontinued. The HRV entropy-based regularity parameters were not altered in this study, suggesting that there were no significant alterations of the REM-NREM ratios between the time stages of the study. These data show that 3 months of melatonin treatment may induce an improvement in cardiac autonomic modulation in melatonin non-proficient patients.